Cuminum cyminum L. Essential Oil: A Promising Antibacterial and Antivirulence Agent Against Multidrug-Resistant Staphylococcus aureus - Sharifi, Aram; Mohammadzadeh, Abdolmajid; Salehi, Taghi Zahraei; Mahmoodi, Pezhman; Nourian, Alireza (Frontiers in Microbiology, 2021)
Cuminum cyminum L. (Cumin) is valued for its aromatic and medicinal properties. There are several reports of antibacterial activity of C. cyminum essential oil (CcEO). Accordingly, the present study was conducted to investigate the mechanism of action/s of the CcEO against multidrug-resistant (MDR) Staphylococcus aureus. Therefore, 10 S. aureus MDR isolates, obtained from different sources, were selected based on the antibiotic susceptibility patterns and the CLSI definition, and subjected to the examinations. Our results exhibited promising bacteriostatic and bactericidal properties of the CcEO. The minimum inhibitory concentration (MIC) and the minimum bactericidal concentration (MBC) values were ranged from 5-10 and 10-20 μl.ml-1, respectively. Scanning electron microscopy (SEM) was used to assess the bacterial cell structure and morphology after the induction with 1/2 MIC concentration of the CcEO. The observed morphological changes appeared to be deformation of the cell membrane and destruction of the cells. In the case of quorum sensing inhibitory (QSI) potential, treatment of S. aureus isolates with the sub-MIC concentrations (1/2 MIC) of the CcEO, significantly reduced the hld expression (3.13 fold downregulation) which considerably controls S. aureus quorum-sensing accessory regulator system. Another virulence factor influenced by the CcEO, was the polysaccharide intercellular adhesin (PIA) production system, as an important component of cell-cell adhesion and biofilm formation. Consequently, the expression level of the intercellular adhesion (ica) locus in the S. aureus cells was examined followed treatment with CcEO. The results showed significant decrease (-3.3 fold) in ica expression indicating that the CcEO could potentially interfere with the process of biofilm formation. Using the ethidium bromide (EtBr) efflux inhibition assay, the S. aureus NorA efflux pump was phenotypically but not genotypically (in qPCR assay) affected by the CcEO treatment.Using Gas Chromatography-Mass Spectrometry (GC-MS) analysis, cuminic aldehyde (38.26%), α,β-Dihydroxyethylbenzene (29.16%), 2-Caren-10-al (11.20%) and γ-Terpinene (6.49%) were the most detected compounds. The antibacterial and anti-virulence action of the CcEO at sub-MIC concentrations means that no microbial resistance will be promoted and developed after the treatment with this agent. These findings revealed that the CcEO is a promising antibacterial agent to control infections caused by the MDR S. aureus strains.